Ischemic heart disease in diabetic and non-diabetic patients - Aozi Feng; Yamilé Peña; Wan Li (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction:Ischemic heart disease has Diabetes mellitus as one of its most important factors, because affects the prognosis, treatment, severity, morbidity and mortality of the first one. Objective: To characterize the influence of diabetes mellitus on ischemic heart disease. Material and Methods: A literature review on the subject was conducted. Results: Diabetes mellitus is confirmed as a highly relevant risk factor for ischemic heart disease. People with diabetes are at the same risk of having a myocardial infarction as people without diabetes who have already had one. Diabetic women are more likely to have ischemic heart disease. There is a higher frequency of Diabetes mellitus in patients with ischemic heart disease aged between 45 and 80 years. Conclusions:Diabetes imposes an increased risk of suffering of ischemic heart disease, makes it more precocious, and imposes diagnostic difficulties and greater risk of complications. Diabetes and ischemic heart disease are illnesses with incidence and prevalence that increase with age. Keywords: Diabetes mellitus, ischemic heart disease, heart disease, diabetics, nondiabetic patients, myocardial perfusion.